2017
DOI: 10.2308/bria-51788
|View full text |Cite
|
Sign up to set email alerts
|

Audit Reviewers' Judgments in Multiple Client Audit Environments

Abstract: This study replicates Bhattacharjee, Maletta, and Moreno (2007), who find that audit preparers are susceptible to contrast effects in a multi-client environment. We demonstrate that auditors in the role of reviewers are also susceptible to contrast effects from a prior client. Audit reviewers' assessments of internal audit quality of a current client were significantly affected by the quality of the internal audit group of a client they previously reviewed. Specifically, when auditors first reviewed a client w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The requirement enforced by the IRBA for auditors of listed entities in 2017, to report further on KAM has further added to the already burdensome tasks of the auditor (Bhattacharjee et al , 2017). This has been described as an effort to convince users of the appropriateness of the audit procedures performed (Bhattacharjee et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement enforced by the IRBA for auditors of listed entities in 2017, to report further on KAM has further added to the already burdensome tasks of the auditor (Bhattacharjee et al , 2017). This has been described as an effort to convince users of the appropriateness of the audit procedures performed (Bhattacharjee et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The requirement enforced by the IRBA for auditors of listed entities in 2017, to report further on KAM has further added to the already burdensome tasks of the auditor (Bhattacharjee et al , 2017). This has been described as an effort to convince users of the appropriateness of the audit procedures performed (Bhattacharjee et al , 2017). Whilst there have been numerous studies examining the virtues of KAM and the related concerns from an international perspective, as well as studies forecasting or attempting to pre-empt what the effect of KAM may be (Kachelmeier et al , 2017; Ratzinger-Sakel and Theis, 2017), few studies have examined this from a South African perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Noting that the majority of uninterrupted work periods (75 percent) involve work on two or more clients, the authors argue that the complex multi‐client, multitasking audit environment may have a profound effect on audit professionals’ decision‐making, potentially leading to dysfunctional outcomes with respect to audit effectiveness and efficiency. Judgment and decision‐making scholars (e.g., Lindberg and Maletta, 2003; O’Donnell and Schultz, 2005; Bhattacharjee et al , 2007, 2017) have investigated those concerns and identified undesirable carryover effects as a common form of information‐processing and recall‐related errors.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Grossman and Welker (2011) extend this research by showing that auditors’ propensity to commit memory conjunction errors is higher when audit evidence is arranged in a causal sequence rather than in a traditional working paper order or random order. However, Bhattacharjee et al (2007, 2017) find that even when memory bits are attributed to the proper client, judgment errors may occur as a result of contrast effects. Specifically, the researchers show that auditors, upon exposure to comparable judgment information, base their assessment of a current client’s information on a comparison of the former with similar information related to a prior client.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation